Impact of liquidity and profitability ratios on stock prices of food and beverage manufacturers - Farman, Fanji; Rahman, Erpi; Nusuki, Ina; Adinegara, Ahmad Andy (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research examines the impact of liquidity and profitability ratios on stock prices of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The study focuses on two key financial ratios: liquidity ratios (current ratio and quick ratio) and profitability ratios (return on assets and return on equity), and their influence on stock price fluctuations. The objective is to analyze how these financial indicators affect investor decisions and market behavior in the food and beverage industry. Liquidity ratios assess a company’s ability to meet short-term obligations, while profitability ratios measure a company’s efficiency in generating profit relative to its assets and equity. By investigating these ratios, the study aims to provide valuable insights into the relationship between financial health and stock price performance in the Indonesian market. This research uses quantitative data obtained from financial statements of selected manufacturing companies, with stock prices being analyzed through closing prices. The findings are expected to contribute to investment strategies and offer recommendations for both investors and companies looking to enhance their market performance. The study also highlights the importance of financial analysis in predicting stock price movements and making informed investment decisions.